2016
DOI: 10.18632/oncotarget.7764
|View full text |Cite
|
Sign up to set email alerts
|

Associations between polymorphisms of long non-coding RNA MEG3 and risk of colorectal cancer in Chinese

Abstract: Maternally expressed gene 3 (MEG3), a long non-coding RNA (lncRNA), is involved in cancer development and metastasis. The objective of the present study was to evaluate whether common single nucleotide polymorphisms (SNPs) in MEG3 could be related with colorectal cancer risk in Chinese. We genotyped six tagSNPs of MEG3 in a colorectal cancer case-control study including 518 cases and 527 control subjects. Multivariate logistic regression analysis was applied to calculate adjusted odds ratios (ORs). We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 24 publications
(27 reference statements)
2
47
0
Order By: Relevance
“…Similarly, Zhang et al demonstrated that increased expression of SPRY4‐IT1 in clear cell renal cell carcinoma led to poor prognosis, and vice versa. Aberrant expression of lncRNA maternally expressed gene 3 (MEG3) in several cancers especially in gastric, colorectal, ovarian, cervical cancers, and OS have been reported recently . However, the precise molecular mechanism(s) behind the altered expression of MEG3 in OS and its function are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Zhang et al demonstrated that increased expression of SPRY4‐IT1 in clear cell renal cell carcinoma led to poor prognosis, and vice versa. Aberrant expression of lncRNA maternally expressed gene 3 (MEG3) in several cancers especially in gastric, colorectal, ovarian, cervical cancers, and OS have been reported recently . However, the precise molecular mechanism(s) behind the altered expression of MEG3 in OS and its function are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the SNPs in MEG3 also participate in the development of different types of cancer. For example, Cao et al discovered that rs7158663 in MEG3 had a strong association with an increased risk of CRC [29]. Studies also demonstrated that rs4081134 in MEG3 was associated with lung cancer susceptibility in a hospital-based case-control study [30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zheng et al [21] investigated rs145204276 in two independent stages, so we treated the study as two independent investigations. Four articles considered not only rs7158663 but also rs4081134 in lncRNA MEG3 [29][30][31][32]. Two articles involved rs1902432, rs16901904, rs4871771, and rs710886 in lncRNA PCAT-1 [27,28].…”
Section: Characteristics Of the Included Studies And Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the association between rs11160608 with colorectal cancer risk was not detected in this study. Furthermore, Zhou et al reported no association between rs7158663 and rs4081134 with neuroblastoma risk (Cao et al, ). In our study, this is the first time to invest the relationship between SNPs in MEG3 and OSCC risk in China.…”
Section: Discussionmentioning
confidence: 99%